Design and Manipulation of a Minimalistic Hydrocarbon Nanocar on Au(111). Issue 6 (15th December 2022) - Barragán, Ana; Nicolás‐García, Tomás; Lauwaet, Koen; Sánchez‐Grande, Ana; Urgel, José I.; Björk, Jonas; Pérez, Emilio M.; Écija, David
Abstract: Nanocars are carbon‐based single‐molecules with a precise design that facilitates their atomic‐scale control on a surface. The rational design of these molecules is important in atomic and molecular‐scale manipulation to advance the development of molecular machines, as well as for a better understanding of self‐assembly, diffusion and desorption processes. Here, we introduce the molecular design and construction of a collection of minimalistic nanocars. They feature an anthracene chassis and four benzene derivatives as wheels. After sublimation and adsorption on an Au(111) surface, we show controlled and fast manipulation of the nanocars along the surface using the tip of a scanning tunneling microscope (STM). The mechanism behind the successful displacement is the induced dipole created over the nanocar by the STM tip. We utilized carbon monoxide functionalized tips both to avoid decomposition and accidentally picking the nanocars up during the manipulation. This strategy allowed thousands of maneuvers to successfully win the Nanocar Race II championship. Abstract : The molecular design and construction of a minimalistic nanocar is described, featuring an anthracene chassis and four benzene derivatives as wheels. After sublimation and adsorption on an Au(111) surface, controlled and fast manipulation of a nanocar is shown along the surface using the tip of a scanning tunneling microscope.